2021
DOI: 10.30585/jrems.v3i3.674
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance disclosure and corporate performance of Nigerian banks

Abstract: Corporate disclosure is a key mechanism of corporate governance. This study examined the effect of corporate governance disclosure (CGD) on the financial performance of commercial banks listed on the Nigeria Stock Exchange. Based on the provisions of the Code of Corporate Governance for Public Companies in Nigeria, 2011 and the Code of Corporate Governance for Banks and Discount Houses 2014, the study developed a disclosure checklist and employed content analysis technique to extract corporate governance (CG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 61 publications
(87 reference statements)
2
9
0
Order By: Relevance
“…Source; author analysis CGI disclosure had a positive and statistically significant effect on ROA in all two estimations as seen in Table 3. These findings are similar to those of (Panchasara & Bharadia, 2013) and (Herbert & Agwor, 2021) who also concluded that corporate governance disclosure positively affected ROA of firms they studied. The results contradicts those of (Harisa et al, 2019) and (Lishenga & Mbaka, 2008) who failed to establish any significant effect of CGI disclosure on ROA.…”
Section: Variables Measurement Are Presented In Tablesupporting
confidence: 89%
See 1 more Smart Citation
“…Source; author analysis CGI disclosure had a positive and statistically significant effect on ROA in all two estimations as seen in Table 3. These findings are similar to those of (Panchasara & Bharadia, 2013) and (Herbert & Agwor, 2021) who also concluded that corporate governance disclosure positively affected ROA of firms they studied. The results contradicts those of (Harisa et al, 2019) and (Lishenga & Mbaka, 2008) who failed to establish any significant effect of CGI disclosure on ROA.…”
Section: Variables Measurement Are Presented In Tablesupporting
confidence: 89%
“…Study done by (Adefemi et al, 2018) also failed to establish any significant effect of CGI disclosure on profitability of Nigerian firms. Herbert & Agwor (2021) determined that the https://www.ilomata.org/index.php/ijtc corporate governance disclosure of board of directors by Nigerian banks had a considerable positive effect on ROA, but it had no meaningful effect on ROE.…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Adefemi et al 2018) also failed to establish any significant effect of CGI disclosure on the profitability of Nigerian firms. Herbert & Agwor (2021) determined that Nigerian banks' corporate governance disclosure of the board of directors had a considerable positive effect on ROA. Still, it had no meaningful effect on ROE.…”
Section: Introductionmentioning
confidence: 99%
“…The undergoing agency problems due to poor governance also hints at the necessity of accountability and the role of an appropriate audit committee that becomes vital in safeguarding owners' interests. The literature suggests that an appropriate audit committee should include independent directors (Herbert & Agwor, 2021;Ahmad et al, 2013). There must be three-member of the audit committee.…”
Section: Introductionmentioning
confidence: 99%
“…Although many scholars concluded that the connection between inside directors' existence and an organization's performance is not undisputed. According to resource dependency theory, it is expected that board size with many links to external surroundings is probable to progress an organizations' success to numerous resources, which result in enhanced corporate governance and organization performance (Bhatt & Bhattacharya, 2015;Chen, Dyball, & Wright, 2009;Herbert & Agwor, 2021;Jackling & Johl, 2009).…”
Section: Introductionmentioning
confidence: 99%